The Statesman's Yearbook 2007 - Turner, B. author. aut Link
1600 p.
Keywords: The Statesman's Yearbook , now in a new, enlarged format, contains profiles of every country in the world and includes 20% new content. All print purchases now receive online access at no extra cost, with a single-user licence giving access to the full text online, updated regularly and fully searchable. For queries - sybinfo@palgrave.com.